Ho jayegi balle balle - Daler Mehndi; Jawahar Wattal; Magnasound; WARNER Music (Malaysia). (India : Magnasound, 1997)
Contains a song with a unique mixture of Western and Punjabi music.
CD 1 : Ho Jayegi Balle Balle.
Koleksi Khas Wiramanja.